A methanogenic protein facilitates the biosynthesis of the silver nanoparticles. (October 2022) - Yan, Xing; Nie, Xinling; Tan, Zhongbiao; Liu, Pei; Li, Xiangqian; Wang, Pixiang; Shi, Hao
Abstract: Silver nanoparticles (AgNPs) have recently attracted worldwide consideration because of their extensive applications. Within the clean production trends, eco-friendly approaches have been provided as an alternative which require less energy consumptions and polluting chemicals. Herein, a purified protein (methyl-coenzyme M reductase D subunit, McrD) from methanogen as bio-reducing agent was used for biosynthesis of AgNPs and the critical factor is mainly related to the characteristics of the protein itself. The obtained optimum condition for synthesis in the mixture was 15 mM silver nitrate and 150 μg mL −1 McrD protein at 30 °C and pH 11 for 24 h incubation. Readily proteins displayed a rapid reduction of silver ion to elementary silver, yielding the spherical AgNPs at a nano-scale of 20 nm. In addition, this eco-friendly synthesized AgNPs possessed a broad-spectrum antimicrobial activity against bacteria and fungi. This work also envisages the possibility of predicting the biological properties of a protein on synthesizing the metal nanoparticles. Overall, this green and facile method is expected to the trend of biosynthesis of synthesizing AgNPs. Graphical Abstract: ga1 Highlights: Structure of the agent protein and properties of silver nanoparticles can explain the synthetic mechanism. Optimization of synthetic condition increases the production and performance. Performance of biosynthesized silver nanoparticles gives the spherical diameter of 20 nm. Biosynthesized silver nanoparticles with distinguished characteristics shows potential applications.